Antibody-drug conjugates: A promising novel therapeutic approach in lung cancer. (January 2022) - Desai, Aakash; Abdayem, Pamela; Adjei, Alex A.; Planchard, David
Highlights: Antibody-drug conjugates (ADCs) are rapidly establishing their place in lung cancer with impressive response rates and survival outcomes in previously treated patients. There are several ADCs currently in clinical trials for NSCLC and small cell lung cancer (SCLC). These ADCs often have different targets which include HER2, HER3, TROP2, CEACAM5, and MET in NSCLC and DLL3 in SCLC. Several novel methods are underway to improve the safety and efficacy of ADCs which include increasing the DAR, the potency of the payload, using more innovative payloads and replacing the antibody. Abstract: Antibody-drug conjugates (ADCs) are rapidly establishing their place and have shown promising preliminary data in lung cancer with impressive response rates and survival outcomes in previously treated patients.There are several ADCs currently in clinical trials for NSCLC and small cell lung cancer (SCLC). These ADCs often have different targets which include HER2, HER3, TROP2, CEACAM5, and MET in NSCLC and DLL3 in SCLC.Here we review the safety, and efficacy of newer ADCs in lung cancer including ado-trastuzumab emtansine, trastuzumab deruxetecan, patritomab deruxetecan, datopotamab deruxetecan, sacituzumab govitecan, SAR408701, Telisotuzumab vedotin, rovalpituzumab tesirine, lorvotuzumab mertansine, and sacituzumab govitecan.  Several novel methods are underway to improve the safety and efficacy of ADCs which include increasing the drug to antibody ratio (DAR), the potency of the payload, using more innovative payloads and replacing the antibody.